Optimization and characterization of enterocin Enterococcus faecalis K2B1 isolated from Toraja’s Belang Buffalo Milk, South Sulawesi, Indonesia - Hasria Alang; JONI KUSNADI; TRI ARDYATI; SUHARJONO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Alang H, Kusnadi J, Ardyati T, Suharjono. 2020. Optimization and characterization of enterocin Enterococcus faecalis K2B1 isolated from Toraja’s Belang Buffalo Milk, South Sulawesi, Indonesia. Biodiversitas 21: 1236-1242. The growing bacterial resistance needs to be controlled with effective antimicrobials. Bacteriocins are proteinaceous toxins produced by bacteria to inhibit the growth of pathogens. Bacteriocin industry has substantially grown, replacing the role of chemical preservatives in enhancing shelf-life and food safety. Bacteriocin produced by genera Enterococcus can be used as an antimicrobial against pathogen. In this study, we used Enterococcus faecalis K2B1 which was first isolated from Toraja’s Belang Buffalo Milk Makassar, Indonesia. The study aimed to optimization and characterization of Enterocinroduced by Enterococcus faecalis K2B1, isolated from Toraja’s Belang buffalo milk. Research Method: including optimization and characterization of antimicrobial metabolite (BLIS) using MRS broth with different initial pH (pH 6, 7 and 8), and partial purification with ammonium sulfate on different concentration (40, 60 and 80 %). Result showed that BLIS production was most optimal on MRS broth at initial pH of 8 after13th hour fermentation, at late exponential phase. BLIS characterization visibly active at high temperatures and very wide range of pH, and disappeared after treating with proteinase-K. Crude had a broad spectrum, was sensitive to Proteinase-K and estimated to have molecular weight of 5 kDa.